Indian mythology and art = اسطورة شناسي وهنر هند - Zekrgoo, Amir Hossein (Iran Academy of Art, MATN Publishing, 2016)
The book is a comprehensive account of Indian mythology and its manifestation in the realm of art compiled in a span of 25 years. It provides a link between India’s faiths and their manifestation in the domain of religious arts and iconography. It is divided into three main parts: Book I = Celestial Deities; Book II = Atmospheric Deities and Book III = Earth Deities. The Book is accompanied with a glossary of technical terms, a comprehensive bibliography, 140 black and white images and line drawings, and 51 color plates.